2006
DOI: 10.1103/physrevlett.96.216401
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Ferromagnetism in Charge-OrderingNa0.55CoO2

Abstract: The magnetic and transport properties are systematically studied on the single crystal N a0.55CoO2 with charge ordering and divergency in resistivity below 50 K. A long-range ferromagnetic ordering is observed in susceptibility below 20 K with the magnetic field parallel to Co-O plane, while a negligible behavior is observed with the field perpendicular to the Co-O plane. It definitely gives a direct evidence for the existence of in-plane ferromagnetism below 20 K. The observed magnetoresistance (MR) of 30 % a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 23 publications
(10 reference statements)
3
56
0
Order By: Relevance
“…Signatures of induced ferromagnetism were reported in laboratory fields even at lower x in the chargeordered regime. 10 Similarly, the misfit compound studied by Limelette et al 6 is near ferromagnetism. 49,50 To see more clearly the dependence of the thermopower on the magnetization, we calculate the thermopower with different magnetizations at 30, 60, and 300 K. We find that the thermopower can be suppressed by ϳ40% in all cases, as shown in Fig.…”
Section: Band Structure Calculations and Boltzmann Transportmentioning
confidence: 94%
See 1 more Smart Citation
“…Signatures of induced ferromagnetism were reported in laboratory fields even at lower x in the chargeordered regime. 10 Similarly, the misfit compound studied by Limelette et al 6 is near ferromagnetism. 49,50 To see more clearly the dependence of the thermopower on the magnetization, we calculate the thermopower with different magnetizations at 30, 60, and 300 K. We find that the thermopower can be suppressed by ϳ40% in all cases, as shown in Fig.…”
Section: Band Structure Calculations and Boltzmann Transportmentioning
confidence: 94%
“…7 Na x CoO 2 displays a rich phase diagram: 8 a Pauli paramagnetic metal ͑x Ͻ 0.5͒ and a Curie-Weiss metal ͑x Ͼ 0.5͒ separated by a charge-ordered insulator ͑at x = 0.5͒, though recently, it was suggested that the boundary between the two metals is at x ϳ 0.60. 9,10 Thus, the sodium cobalt oxides are currently of great interest from both application and physics points of view. Na x CoO 2 exhibits an unusual combination of transport properties which are conventionally interpreted as either metallic or insulating features.…”
Section: Introductionmentioning
confidence: 99%
“…[1, 2, 3, 4] The complex physical properties include the unconventional superconductivity in water-intercalated Na 0.35 CoO 2 , [5] temperature-dependent Hall effect, [3,6] large negative MR in (Bi,Pb) 2 M 2 Co 2 O y (M=Sr and Ca) and Ca 3 Co 4 O 9 ,[2, 6,7] large thermopower (TEP) with low resistivity,[1, 2] and complicated magnetic structure, [8,9,10] etc. These triangular cobaltites have the common structural unit of CdI 2 -type hexagonal [CoO 2 ] layer, which is composed of edge-shared CoO 6 octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…When the emission of synchrotron radiation occurs coherently in the structure of a bunch, very high-power radiation is generated. A coherent synchrotron radiation (CSR) source can be realized at the storage rings by using short-bunch beam optics [7][8][9] or imprinting electron density modulation by interaction with a laser pulse [10,11]. The electron-linac-based system has advantage in producing a short-bunch beam.…”
Section: Introductionmentioning
confidence: 99%